Breathe - Beni Rusani Dr (MPH Group Publishing Sdn Bhd, 2021)
I'm dying. For a brief moment, his muddled mind became clear and he could think. Stay afloat, breathe. Just keep breathing. Dr Adam is a cardiologist who knows how to help others. The only thing he can't fix is himself. When a heart attack threatens his life, Adam is given a chance to look at his life to rediscover the friendship and the love he lost. In his darkest hours, friends and strangers are racing against time to save him. However, the key to his survival and future might lie in his past.